2016
DOI: 10.1016/j.psyneuen.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol and self-reported stress in healthy, working adults

Abstract: Chronic stress can be important in the pathology of chronic disease. Hair cortisol concentrations (HCC) are proposed to reflect long term cortisol secretion from exposure to stress. To date, inconsistencies in the relationship between HCC and self-reported stress have been attributed to variation and limitations of perceived stress measurement. We report data from employees of two large public sector worksites (n=132). Socio-demographic, health, lifestyle, Perceived Stress Scale (PSS), and work-related Effort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 52 publications
7
52
0
3
Order By: Relevance
“…Inada et al [50] reported a 77.8% retention rate in their 6-month study. Gidlow et al [54] reported on a 12-week EMA study that was focused on stress among 153 healthy working adults that achieved a retention rate of 89.5%, confirming that, similar to our study, high rates of retention can be achieved in longer studies. Several studies that ranged from 4 [55-57] to 8 [58] to 18 weeks [59] did not report retention rates.…”
Section: Discussionsupporting
confidence: 91%
“…Inada et al [50] reported a 77.8% retention rate in their 6-month study. Gidlow et al [54] reported on a 12-week EMA study that was focused on stress among 153 healthy working adults that achieved a retention rate of 89.5%, confirming that, similar to our study, high rates of retention can be achieved in longer studies. Several studies that ranged from 4 [55-57] to 8 [58] to 18 weeks [59] did not report retention rates.…”
Section: Discussionsupporting
confidence: 91%
“…We therefor expected major stress to more strongly affect hair biology than highly acute stress paradigms. Populations affected by chronic and severe stress paradigms such as traumatic experience, work related stress or the stress of care giving [3033] appeared too diverse to meet the requirement of a small, sociobiologically homogeneous pilot sample population. We therefor chose the final exam for German medical students, as a naturalistic paradigm for perceived stress in life [3437].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, excess cortisol secretion, resulting from fear of violent crime, can impair glucose metabolism, promote abdominal fat deposition, and increase vascular reactivity . These physiologic processes can occur unconsciously and may be difficult for individuals to quantify by self‐report . Prior studies have also used self‐reported measures of health, which may lead to significant underestimation of health effects in communities with lower education (eg, poor health literacy) and unreliable access to health care …”
mentioning
confidence: 99%
“…14,15 These physiologic processes can occur unconsciously and may be difficult for individuals to quantify by self-report. 16,17 Prior studies have also used self-reported measures of health, 7,10 which may lead to significant underestimation of health effects in communities with lower education (eg, poor health literacy) 18 and unreliable access to health care. 19 Other studies have used objective measures of crime, but they have not examined the different types of crime encountered (eg, violent crime and homicide) or demographic groups targeted (eg, elderly people and women), limiting comparative inference.…”
mentioning
confidence: 99%